Hot deformation behavior of In/CupIn/In composite thermal interface materials - Jie Zhang; Yulin Liu; Zhongnan Xie; Hong Guo; Mingmei Sun; Hui Yang; Xinbo He (Journal of Materials Research and Technology, 2025)
The hot compressive deformation behavior of In/CupIn/In (pure Indium–Copper particle reinforced Indium matrix composites-pure Indium) composite materials prepared by hot press sintering was systematically investigated in the temperature and strain rate ranges of 20–110 °C and 0.01–10 s−1. The constitutive model and processing map were established, and the microstructure evolution was analyzed. The results show that the flow stress of the In/CupIn/In composite materials exhibit significant dependence on deformation rate and temperature. The strain-corrected Arrhenius model can accurately describe the plastic flow process. The In matrix grain size is sensitive to deformation conditions. Uniform equiaxed In grains without preferred orientation can be formed at 110 °C rolling temperature and 0.1 mm/s rolling speed, representing the optimal rolling parameters. The primary instability mechanisms are interfacial cracking and local plastic flow. The rolled In/CupIn/In composite material exhibits defect-free microstructure with low interfacial thermal resistance of 0.52 Kcm2/W, which is 13.6 % lower than that of pure In.